Storytelling Methods and Language Development in Early Childhood Education: Metode Bercerita dan Perkembangan Bahasa dalam Pendidikan Anak Usia Dini - Sabrina Rizky Amalia; Evi Destiana (Academia Open, 2025)
General Background Early childhood represents a critical period for rapid language acquisition that supports communication, cognitive growth, and social interaction. Specific Background In kindergarten settings, storytelling is frequently applied as a learning method using visual and audio-visual media to stimulate listening and speaking activities among children aged 4–5 years. Knowledge Gap Despite routine classroom application, systematic descriptions of how storytelling methods are implemented and how language development outcomes manifest in daily practice remain limited. Aims This study aims to describe the implementation of storytelling methods and the observable language development of children aged 4–5 years at TK Aisyiyah Bebekan–Sepanjang. Results Using a qualitative descriptive approach through observation, interviews, and documentation, the findings show that daily storytelling sessions lasting 15–20 minutes at the beginning of learning activities support improvements in listening skills, vocabulary acquisition, speaking confidence, and sentence construction. The use of picture books, picture cards, and audio-visual media creates an interactive and engaging learning atmosphere that encourages active child participation. Novelty This study provides a contextualized description of routine storytelling practices integrated with varied media in an early childhood classroom and links them to concrete indicators of language development. Implications The findings suggest that structured and consistent storytelling activities can serve as a practical pedagogical reference for early childhood educators seeking to support language development through enjoyable and participatory learning experiences. Highlights: Routine Storytelling Sessions Foster Sustained Attention and Comprehension During Classroom Activities. Varied Visual and Audio-Visual Media Support Active Participation and Verbal Expression. Children Demonstrate Growth in Word Usage and More Organized Sentence Formation. Keywords: Storytelling Method, Language Development, Early Childhood Education, Listening Skills, Vocabulary Acquisition